A study on the machining characteristics of induction and laser-induction assisted machining of AISI 1045 steel and Inconel 718. (August 2018) - Baek, Jong-Tae; Woo, Wan-Sik; Lee, Choon-Man
Abstract: Difficult-to-machine materials are being widely used in various industries. However, these materials are much more difficult to machine using conventional machining (CM) methods than other common materials, because of their superior material properties such as high strength, stiffness and brittleness. Thermally assisted machining (TAM) methods have been developed to address this problem. Laser assisted machining (LAM) is a type of TAM process in which a workpiece is locally softened by a laser heat source in front of the cutting tool. The method is an effective way to enhance machinability when processing various difficult-to-cut materials. Two other approaches, induction assisted machining (IAM) and laser-induction assisted machining (LIAM), were analyzed and experimentally investigated in this study to compare their efficiency with that of CM for two materials, AISI 1045 steel and Inconel 718. It was found that cutting force was decreased and surface quality was improved when the IAM and LIAM were used.